Fluorescence Quenching of Sulforhodamine Dye over Graphene Oxide and Boron Nitride Nanosheets. Issue 13 (12th January 2016) - Thangaraj, Vidhyadevi; Bussiere, Jules; Janot, Jean‐Marc; Bechelany, Mikhael; Jaber, Maguy; Subramanian, Sivanesan; Miele, Philippe; Balme, Sebastien
Abstract: We report the fluorescence quenching of sulforhodamine 640 (SR 640) supported on graphene oxide (GO) and boron nitride (BN) nanosheets (NSs). The synthesis and characterization of both materials are described. X‐ray diffraction (XRD), Raman spectroscopy, atomic force microscopy (AFM), transmission and scanning electron microscopy (TEM and SEM), and the Brunauer–Emmett–Teller (BET) method were used. The photophysical properties, such as the fluorescence lifetime and anisotropy of the SR dye over the synthesized materials, are reported. The observed fluorescence quenching of the SR dye over GO and BN occurs through an electron‐transfer process. Fluorescence decay analysis of SR revealed different behavior in the presence of GO and BN NSs. Adsorption of the dye on GO NSs leads to a non‐fluorescent complex, whereas adsorption of the dye on BN NSs results in quenching induced by a decrease in the fluorescence lifetime of the dye. Abstract : We report the fluorescence quenching properties of sulforhodamine 640 (SR 640) supported on graphene oxide (GO) and boron nitride (BN) nanosheets (NSs). For GO, the adsorption of dye leads to a non‐fluorescent complex, whereas for BN NSs the observed quenching is induced by a decrease in the fluorescence lifetime of the dye.